Medical-psychological support of the children with consequences of traumatic brain injury - K. V. Aymedov (Kazimierz Wielki University, 2017)
Ukrainian statistics for 2008 - 2016 have been analyzed. It has been revealed that about 100000 people are injured in traumatic brain injury (TBI) annually in this country, and 11.5-13.5 thousands of them are children under 15 years old. The author emphasizes that TBI is a complex medical and social problem due to its high prevalence in all age groups, including children and adolescents, variety of its possible consequences. Thus the prediction of TBI consequences is a top urgent problem. Predicting TBI consequences is a tool of the treatment effectiveness monitoring and further support of this category of patients. Being a systemic scientific process, forecast supports further researches, provides constructive interaction of practical medicine and psychology, implements the development of technical progress achievements and creates conditions for economic development, contributes to the formation of a multidisciplinary approach in solving the urgent issues of TBI in general and in children in particular .